2011
DOI: 10.3892/mmr.2011.424
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 enhances intracellular Fas-mediated apoptotic signals in HHUA human endometrial epithelial cells

Abstract: Abstract. Several endometrial signal transducer and activator of transcription 3 (STaT3)-activating cytokines are reported to be essential for blastocyst implantation, with inhibition of STaT3 activation in the endometrium also reported to prevent implantation. To investigate STaT3 signals in endometrial epithelial cells, the activation and inactivation effects of STaT3 signals were examined in the human endometrial epithelial cell line HHua, which is thought to retain many of the intracellular signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that PAB induces growth inhibition, cell cycle arrest and apoptosis in a variety of cancer cell lines, including breast cancer, colon cancer, hepatocellular carcinoma and melanoma cells (18)(19)(20)(21)(22). In the present study, the effects of PAB on cell growth and death in U937 cells (a Apoptosis, or programmed cell death, is important in a variety of physiological processes during fetal development and in adult life (23)(24)(25). Cell shrinkage, chromatin condensation and nuclear fragmentation are the morphological hallmarks of apoptosis (26).…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have demonstrated that PAB induces growth inhibition, cell cycle arrest and apoptosis in a variety of cancer cell lines, including breast cancer, colon cancer, hepatocellular carcinoma and melanoma cells (18)(19)(20)(21)(22). In the present study, the effects of PAB on cell growth and death in U937 cells (a Apoptosis, or programmed cell death, is important in a variety of physiological processes during fetal development and in adult life (23)(24)(25). Cell shrinkage, chromatin condensation and nuclear fragmentation are the morphological hallmarks of apoptosis (26).…”
Section: Discussionmentioning
confidence: 57%